Study on the Method of Calculation of the Additional Mass of Parachute - Hyo Il Pak; Chol Guk Mun; Sol Song Pak (International Journal of Machine Systems and Manufacturing Technology, 2025)
As is well known, the air drag experienced by a parachute when it is open is one of the important parameters that must be taken into account in studying the parachute opening process. If this term is not calculated correctly, it can have a negative effect on the parachute canopy, and may lead to errors in the number of parachute strings, the nominal diameter of the parachute, and the material selection, and eventually to parachute failure. Generally, there are several hydrodynamic methods in this calculation, including modeling the recovery system dynamic equations based on the drag characteristics in the calculation of canopy forces and calculating the load change during parachute opening. Thus, it can be seen that the accurate determination of the added mass is crucial for the calculation of the forces that the canopy experiences during parachute opening. In the past, the added mass was based on the assumption of an ideally expanded canopy shape using the added mass coefficient method, but no research on the added mass coefficient method has been developed so far. To this end, this paper formulates the concept of the additional mass of the parachute and develops the UAV-parachute system equations of motion. Also, through numerical calculations, two engineering calculations of the added mass are presented : the internal mass method and the expansion radius method. Considering both methods, it was concluded that the dilatation radius method is better for calculating the radial and axial additional mass of the parachute.
Keywords: Aerodynamic decelerator; arbitrary Lagrangian Euler method (ALEM); infinite mass; open process; parachute rope